Polymerization Assisted by Upconversion Nanoparticles under NIR Light - Demina, Polina (Molecules, 2019)
Photopolymerization of nanocomposite materials using near infrared light is one of the unique technologies based on the luminescent properties of lanthanide-doped upconversion nanoparticles (UCNPs). We explored the UCNP-triggered radical polymerization both in oligomer bulk and on the nanoparticle surface in aqueous dispersion. Core/shell UCNPs NaYF(4):Yb(3+) and Tm(3+)/NaYF(4) with emitting lines in the ultraviolet and blue regions were used to activate a photoinitiator. The study of the bulk photopolymerization in an initially homogeneous reaction mixture showed the UCNP redistribution due to gradient density occurring in the volume, which led to formation of UCNP superlattices and spheres “frozen” in a polymer matrix. We also developed a strategy of “grafting from” the surface, providing polymer shell growth directly on the nanoparticles. The photosensitization of the endogenous water-soluble photoinitiator riboflavin by the resonance energy transfer from UCNPs was demonstrated in the course of monomer glycidyl methacrylate polymerization followed by photocrosslinking with poly(ethylene glycol) diacrylate on the nanoparticle surface.